2017
DOI: 10.1177/1010539517735414
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric Characteristics and Physical Fitness in Rural and Urban 11- to 16-Year-Old Melanesian Adolescents: A Cross-sectional Study in New Caledonian Schools

Abstract: We evaluated anthropometric characteristics and physical fitness in 556 Melanesian adolescents from rural and urban New Caledonia to build health education programs focused on physical activity. In 2013, body weight, height, skinfold thickness, lean body mass (LBM), percentage fat body mass (%FBM), physical fitness (power, agility, speed, maximal aerobic speed [MAS], estimated VO), and self-reported physical activity were assessed. Rural adolescents were significantly shorter and faster, had lower weight, %FBM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 23 publications
4
11
0
1
Order By: Relevance
“…In general, it was observed that preschoolers in the urban environment had higher values in height and SRT (Figure 1 and Figure 2). These data coincided with studies of the Kenya and Caledonia populations [20,40], but not with previous research in Spain, where children from rural areas had higher anthropometric and physical condition values than those from the urban environment [22,23]. The abovementioned studies included ages of primary and secondary education.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In general, it was observed that preschoolers in the urban environment had higher values in height and SRT (Figure 1 and Figure 2). These data coincided with studies of the Kenya and Caledonia populations [20,40], but not with previous research in Spain, where children from rural areas had higher anthropometric and physical condition values than those from the urban environment [22,23]. The abovementioned studies included ages of primary and secondary education.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, the environment of residence (rural versus urban) might also influence the level of physical fitness. Actually, there was information on the effect of the environment in different countries such as the United Kingdom [17], Taiwan [18], Kosovo [19], New Caledonia [20], Croatia [21], and Spain [22,23]. The size of the population in the place of residence might be associated with opportunities for access to sports facilities, occasions for physical activity, lifestyle, or eating habits [15,22].…”
Section: Introductionmentioning
confidence: 99%
“…Substitution of traditional food energy sources with highly processed foods high in sugar, fat and salt are consistent with Western diets consumed in countries where obesity is epidemic. These dietary changes might explain the high percentage of overweight and obesity (38.1% for rural and 31.7% for urban adolescents) observed in this study and those of other studies [ 10 , 11 , 12 ].…”
Section: Discussionsupporting
confidence: 65%
“…These combined lifestyle variables are the root cause (but not unique) of noncommunicable diseases, and the young Pacific population is extremely exposed. The prevalence of overweight and obesity is very high in New Caledonian adolescents (from 36% to 43%, depending on age and the reference used to assess overweight) [ 9 , 10 , 11 ], and this is particularly the case for Melanesians. Indeed, a recent study showed that the prevalence of overweight/obesity was higher in 11 to 16-year-old Melanesian and Polynesian adolescents than in Caucasian adolescents, respectively, 38.2%, 30.4% and 21.3% [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation